Pengaruh Utang Luar Negeri Terhadap Perekonomian dan Kemiskinan - Dedi Junaedi; Faisal Salistia (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2019)
This study aims to: analyze the significance of the effect of foreign debt on economic growth and poverty levels in Indonesia; examine whether different regimes of the Angagran system affect the management of foreign debt in the context of stimulating the economy and alleviating poverty; and explore what budget system is most behind in encouraging the national economy and poverty alleviation. The method used is descriptive-quantitative analysis using a dummy variable multiple regression test, with genus samples and times series data 1949-2018, data taken from Bank Indonesia (BI) , National Development Planning Agency (Bappenas), Central Statistics Agency (BPS), World Bank and other reference sources. The research results show that foreign debt and inflation have a correlation with the condition of the national economy, specifically the value of Indonesia's Gross Domestic Product (GDP) and the level of poverty. Debt and inflation tend to increase the value of GDP and reduce poverty. This applies to all regimes of the government budget system. The difference in the budget system regime has a real and positive effect in terms of debt governance as an economic driver and poverty alleviation, in achieving GDP, performance-based budgeting regimes, integrated budget regimes and balanced budgets have better impacts than better than program-based budgeting regimes. The best budget system sequences are: performance based budgeting, integrated budgeting, budgeting budgeting and program based budgeting. In poverty alleviation, a balanced budget regime, a performance based budget and an integrated budget are more than a program based budget regime. The order of the best budget system to support poverty alleviation is a balanced budget system, a performance based budget, an integrated budget and a program based budget.